Analysis of Management of Demand and Production Capacity : Study on One of The MSME Laundry In Batam City - Alex Alex; Amelia Putri; Ricky Tan; Lutfy Setia Wahyudi; Jovina Jovina (Acman: Accounting and Management Journal, 2023)
many demand . Batam is famous for industrial workers who work from morning untilto the morning again. so they don't have time to do their own homework. So laundry is one of the problem solvers for busy workers in Batam City.